Optimization of Conservation Farming at Coastal Land in Bantul Regency - Widodo, Aris Slamet (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No. 2, Agustus 2018 (pp. 147-253), 2018)
The aims of this study are to analyse the optimum resource allocation of conservational farming at coastal lands and to examine the influence of substitution of external input by internal input toward the income of farmers at coastal areas. The research method applied in this study was a survey method. The site of this study was determined purposively covering the areas along Samas coastal line at Srigading and Gadingsari Villages, Sanden District, Bantul Regency of Yogyakarta Special Province. The sampling was conducted trough proportional random sampling and based on the number of population, the samples were then determined 110 people. The findings conclude that the optimum resource allocation of conservational farming at sandy coastal areas at rainy season is by planting shallot 0.052 ha (52%), eggplant 0.032 ha (32%) and sweet potatoes 0.016 ha (16%), In the dry season 1, the optimum resource allocation is by planting shallot 0.022 ha (22%), chili 0.022 ha (22%) and sweet potatoes 0.051 ha (51%). In the dry season 2, optimum allocation of conservational farming is by planting chili 0.062 ha (62%) and sweet potatoes 0.038 ha (38%). The optimum resource allocation has influence the substitution of inorganic nutrient element by organic nutrient elements of: 28.1% N, 28.28% P and 20,55 % K. The maximum income in the optimal resource allocation of input is Rp 11,647,110.-/year.
Keywords: Optimization; conservation farming; coastal land